2013
DOI: 10.1186/1475-2891-12-142
|View full text |Cite
|
Sign up to set email alerts
|

Effects of coenzyme Q10 supplementation (300 mg/day) on antioxidation and anti-inflammation in coronary artery disease patients during statins therapy: a randomized, placebo-controlled trial

Abstract: BackgroundHigh oxidative stress and chronic inflammation can contribute to the pathogenesis of coronary artery disease (CAD). Coenzyme Q10 is an endogenous lipid-soluble antioxidant. Statins therapy can reduce the biosynthesis of coenzyme Q10. The purpose of this study was to investigate the effects of a coenzyme Q10 supplement (300 mg/d; 150 mg/b.i.d) on antioxidation and anti-inflammation in patients who have CAD during statins therapy.MethodsPatients who were identified by cardiac catheterization as having … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
96
3
5

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 150 publications
(108 citation statements)
references
References 35 publications
4
96
3
5
Order By: Relevance
“…In another study, CoQ10 supplementation significantly reduced the IL-6 protein and TGF-b1 and Lep mRNA levels [6]. In addition, our study was in agreement with findings in cardiac tissue [23], and CoQ10 is known to have anti-inflammatory properties in mouse liver [24] and human plasma [25]. Also, gene expression of TNF-a were significantly decreased following CoQ10 intake in an experimental model of multiple sclerosis for three weeks [26].…”
Section: Discussionsupporting
confidence: 89%
“…In another study, CoQ10 supplementation significantly reduced the IL-6 protein and TGF-b1 and Lep mRNA levels [6]. In addition, our study was in agreement with findings in cardiac tissue [23], and CoQ10 is known to have anti-inflammatory properties in mouse liver [24] and human plasma [25]. Also, gene expression of TNF-a were significantly decreased following CoQ10 intake in an experimental model of multiple sclerosis for three weeks [26].…”
Section: Discussionsupporting
confidence: 89%
“…31,32 Thus, as well as reducing the risk of cardiovascular problems in patients with liver disease, CoQ10 supplementation may also benefit the disease process within the liver by reducing inflammation and oxidative stress, key factors in the pathogenesis of NAFLD. 33 Yesilova et al 34 found that blood CoQ10 levels were depleted in NAFLD patients, with the decrease in CoQ10 correlating with increased liver inflammation and cirrhosis.…”
Section: Coq10 Diabetes and Liver Diseasementioning
confidence: 99%
“…It is unique among naturally occurring and it is synthesized de novo in animals [7]. Studies have shown that the CoQ10 has free radical-scavenging activities, liver injuryreducing properties and endothelial dysfunction improving [8].…”
Section: Introductionmentioning
confidence: 99%